Effects of some mineral deficiencies on the development of the soybean plant, Glycine max (L.) Merril cv Santa Rosa - Rodrigues, S. D.; Rodrigues, J. D.; Ono, E. O.; Pedras, J. F.; deMoraes, JAPV; Delachiave, MEA (Fundacion Romulo Raggio, 1997)
The present work studies Ca, B and Zn omission on the development of soybean plants (Glycine max (L.) Merrill cv Santa Rosa). The experiment was carried out as hydroponic culture, viith complete Hoagland & Arnon nutrient solution nr. 2 (C), lacking calcium (-Ca), lacking boron (-B) or lacking zinc (-Zn), a total of 4 treatments. Seven samplings were made to determine: total dry matter (g), root dry matter (g), stem dry matter (g) and leaf dry matter (g). Results showed that Ca and B omissions decreased dry weight. Lack of Zn did not affect dry weight.
Keywords: soybean; nutritive solution; calcium; boron; zinc; nutritional omission